2007
DOI: 10.5694/j.1326-5377.2007.tb00802.x
|View full text |Cite
|
Sign up to set email alerts
|

Consensus recommendations for the diagnosis, treatment and control of Mycobacterium ulcerans infection (Bairnsdale or Buruli ulcer) in Victoria, Australia

Abstract: Mycobacterium ulcerans causes slowly progressive, destructive skin and soft tissue infections, known as Bairnsdale or Buruli ulcer (BU). Forty‐six delegates with experience in the management of BU attended a 1‐day conference in Melbourne on 10 February 2006, with the aim of developing a consensus approach to the diagnosis, treatment and control of BU. An initial draft document was extended and improved during a facilitated round table discussion. BU is an environmental infection that occurs in specific locatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
87
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(90 citation statements)
references
References 29 publications
3
87
0
Order By: Relevance
“…Cases of BU are usually clustered around swamps and slow-flowing water and while the mode of transmission of M. ulcerans is unknown, evidence to date suggests, fish [5], snails [6] and certain carnivorous aquatic insects [7],[8] can all harbour the bacterium. Recent studies in Australia suggest mosquitoes may play a role in transmission [9],[10].…”
Section: Introductionmentioning
confidence: 99%
“…Cases of BU are usually clustered around swamps and slow-flowing water and while the mode of transmission of M. ulcerans is unknown, evidence to date suggests, fish [5], snails [6] and certain carnivorous aquatic insects [7],[8] can all harbour the bacterium. Recent studies in Australia suggest mosquitoes may play a role in transmission [9],[10].…”
Section: Introductionmentioning
confidence: 99%
“…However, country-wide data can obscure local variation in climate and the issue of seasonal trends needs to be more closely investigated at the local level. The unknown incubation period for Buruli ulcer, which may vary from 2 weeks to 7 months [92], [93], also makes it difficult to analyze seasonal factors with Buruli ulcer occurrence. Duker et al [4], and more recently Marion et al [94], discussed seasonal variations and M. ulcerans infections reported from different countries and concluded that there may be a temporal relationship between BU incidences and relatively dry periods; however, it also has been reported that M. ulcerans infections occurred mainly after flooding events [9], [16], [33], [34], [95].…”
Section: Resultsmentioning
confidence: 99%
“…However, in Marion et al [93], only one endemic area and one non-endemic area were evaluated, suggesting no replication, and thus, a limitation to testing how variable M. ulcerans is among endemic versus non-endemic areas/villages. This makes it difficult to compare to studies by Williamson et al [67] and Benbow et al [68] where multiple replicate sites were evaluated to test for M. ulcerans variability in standardized ecological samples.…”
Section: Resultsmentioning
confidence: 99%
“…This hypothesis is consistent with several results from environmental studies. In Australia, M. ulcerans infection is now considered a zoonosis transmitted from possum to human by mosquitoes [21], [22].…”
Section: Discussionmentioning
confidence: 99%